Colloids launches new range of engineering polymer masterbatches at Chinaplas. Issue 6 (June 2018) - Unknown
Abstract : British masterbatch, compounds and additives manufacturer Colloids used the platform provided by the recent Chinaplas 2018 trade fair to launch two new product ranges aimed at high-performance applications in the key automotive, electrical & electronics (E&E) and electrostatically dissipative (ESD) packaging, storage and distribution markets.